The futures of American studies - Pease, Donald E.; Wiegman, Robyn (New Americanists., 2002)
Originating as a proponent of U.S. exceptionalism during the Cold War, American Studies has now reinvented itself, vigorously critiquing various kinds of critical hegemony and launching innovative interdisciplinary endeavors. The Futures of American Studies considers the field today and provides important deliberations on what it might yet become. Essays by both prominent and emerging scholars provide theoretically engaging analyses of the postnational impulse of current scholarship, the field's historical relationship to social movements, the status of theory, the state of higher education in the United States, and the impact of ethnic and gender studies on area studies. They also investigate the influence of poststructuralism, postcolonial studies, sexuality studies, and cultural studies on U.S. nationalist--and antinationalist--discourses. No single overriding paradigm dominates the anthology. Instead, the articles enter into a lively and challenging dialogue with one another. A major assessment of the state of the field, The Futures of American Studies is necessary reading for American Studies scholars.--Publisher website.